Analisis Karakterisitik Lingkungan dan Pengembangan Budidaya Ikan Sistem KJA Di Dusun Wael Kabupaten Seram Bagian Barat - Karepesina, Musa; Saimima, Nur Asyah; Manuhutu, Desry Natalia; Salampessy, Naiboki; Lanuhu, Hajirun (Universitas Batangahari Jambi, 2024)
Research on the analysis of environmental characteristics of KJA system fish farming in Wael Sub Village, West Seram Regency aims to analyze internal and external environmental factors of aquaculture development with KJA system in Wael Hamlet and formulate strategies and priorities for the development of aquaculture with KJA system in Wael Sub Village, West Seram Regency. To analyze the potential for aquaculture development using the EAA (Ecosystem Approach to Aquaculture) method approach. Aquaculture development according to FAO (2010), has shifted from conventional approaches to the ecosystem approach to aquaculture (EAA). The development of aquaculture with the KJA system in the waters of Wael Sub Village by 12 groups of farmers is in accordance with the allocation of space, land suitability and supported by good water quality conditions. Socially, aquaculture businesses with KJA absorb local labor. Economically, this business is profitable. There are already formal institutions in aquaculture management with their respective duties and authorities. The results of the analysis with the EAA approach that assesses the existing conditions of mariculture business development using the KJA system in Wael Sub Village show that this business still has the potential to continue to be developed.